Chitosan as natural coagulant in the removal of heavy metal - Ong, Jeffrey Min Han (2024)
Heavy metal contamination in wastewater poses serious environmental and health risks. Coagulation stands out as one of the most commonly used techniques in industry for heavy metal removal. Traditional coagulants like alum and iron chloride are unsustainable and may contribute to health issues. Chitosan, a natural coagulant derived from crustaceous shells such as crabs and shrimps, has emerged as a promising alternative. This study focuses on investigating the impact of various process parameters (chitosan dosage, pH, and the type of acid used) on chitosan’s effectiveness as a coagulant in removing nickel from wastewater generated by a local electronic components manufacturer. The results suggest that chitosan alone can serve as a highly efficient primary coagulant, eliminating the necessity for supplementary aids such as alum. This is evidenced by the considerably lower removal efficiency achieved with the optimal chitosan/alum composite ratio of 0.4:0.6, which stood at only 68.62 % while pure chitosan was able to achieve a removal rate of 82.54 %. Moreover, sulfuric acid (H2SO4) was identified as the most suitable acid due to its diprotic nature. Optimal conditions of using pure chitosan achieved a 96.13 % nickel removal with a chitosan dosage of 40 g/L, initial nickel concentration of 100 mg/L, and pH of 7. Interestingly, the dosage of chitosan could be reduced to 30 g/L if the wastewater underwent oxidation before the coagulation process. Further analysis using scanning electron microscopy coupled with energy dispersive X-ray spectrometry (SEM-EDX) confirmed the presence of nickel elements in the chitosan sludge, validating the efficacy of chitosan as a natural coagulant in removing heavy metals from wastewater. In summary, chitosan emerges as a promising natural coagulant for removing heavy metals, highlighting the need for further investigation in future studies.